Plan de acción para el fortalecimiento del sector turístico productivo afectado por el terremoto del cantón Bolívar. - Intriago Bravo, Jeysson Orlando (2018)
The main objective of this research is to design an action plan to strengthen Bolívar's productive tourism sector, based on three phases: tourism diagnosis, where the information was collected from 88 establishments (restaurants, hostels, recreation centers) through files and surveys to owners, determining that the work of the GAD tourism subsystem is deficient; the perception of tourists was known by applying surveys, highlighting the problems during their visit; internal and external factors were identified through the use of the EFE, EFI, SWOT matrices; the SPSS program was used to tabulate the data. Elaboration of the action plan structured by mission, vision, objectives, strategic actions for which aspects for tourism development were taken into account including political factors, sustainability, marketing, inclusion and socialization in such a way that they admit the fulfillment of the general objective of the investigation. In the last phase of monitoring and control, strategic actions were established in the action plan considering political, environmental, marketing and social inclusion aspects. As results of the investigation are: the profile of the visitor (provincial origin, occupation of the employee, age between 26 and 30 years), who highlighted problems such as disorganization, lack of basic services, signage and carelessness by authorities; based on these results for the evaluation, strategies were generated, actions were considered relevant in the application of norms and policies through evaluation cards and quarterly reports, as well as monitoring of training, all for the achievement of the objectives.